Worshipping the Kuladevata and Kuladevi - Mumbai Archive Project Team (Jio Institute, 2024)
The most important part of the house is the shrine of the kuladevata (male clan deity) or the kuladevi (female clan deity). Kuldevatas protect one’s kula (clan), gotra (lineage), family, and children from misfortune. The shrine also features an image of Ganapati, a universally worshipped Hindu deity across Maharashtra.